Preparation method and application of a water-based Pickering emulsion type hydration heat inhibition material

Through the use of hydrophobic hydraulic thermal inhibitory materials in large -volume concrete construction, it solves the problem of heat and heat release during cement hydration, and achieves the effect of reducing temperature cracks and maintaining concrete strength.

CN119161128BActive Publication Date: 2025-01-24CNBM ZHONGYAN TECH +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411597118.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-24
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

During the construction of large volume concrete, concentrated heat release during cement hydration leads to large temperature differences between the inside and outside, resulting in temperature stress and cracks. The existing hydration heat suppression materials are prone to uneven dispersion, affecting the use effect.

Method used

The water -based Pickering lotion -type hydrophilized thermal inhibitory material is used. By using polyester -based products in the lotion and nano -jelly gel or suspension as the main ingredient, it forms a stable oil and water interface to control hydrophilic heat release and cumulative accumulation. Put heat.

Benefits of technology

This material has good stability and can significantly reduce the peak heat release rate of hydration heat, the cumulative heat release of hydration heat and the peak adiabatic temperature rise, reduce the occurrence of temperature cracks, and has little impact on the strength of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the technical field of cement-based building material admixtures, and specifically discloses a preparation method and application of a water-based Pickering emulsion type hydration heat inhibitor material. A hydration heat inhibitor material disclosed in the present application specifically includes the following components in parts by weight: 90-110 parts of water, 5-20 parts of oil phase cosolvent, 0.1-0.7 parts of solubilizer, 20-100 parts of colloidal emulsifier, and 0.5-15 parts of oil phase component; the oil phase component is prepared from anhydride, diol, inhibitor, and catalyst in a molar ratio of 0.5-3: 0.7-1.3: 0.01-0.15: 0.15-0.75. The hydration heat inhibitor material prepared in the present application has good stability. The hydration heat release rate peak value, hydration heat cumulative heat release, and adiabatic temperature rise peak value of the hydration heat inhibitor material during the application process are greatly reduced, and the strength reduction value is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of cement-based building material admixtures, and in particular to a hydration heat inhibition material and a preparation method and application thereof. Background Art

[0002] In many special construction projects, such as water conservancy projects, super high-rise buildings and underground structure projects, large-volume concrete is needed as the basic material. However, due to the large concentrated heat release during the hydration of concrete cement, the internal heat is difficult to dissipate in time, resulting in a large temperature difference between the inside and outside of the concrete, generating temperature stress and causing large-volume concrete to crack. At present, the main way to control the generation of temperature cracks is to control the concentrated heat release of cement hydration and reduce the temperature difference between the inside and outside of large-volume concrete.

[0003] Hydration heat inhibitors are functional materials that can inhibit the hydration process of cement and control the hydration heat release rate, which can effectively reduce the temperature gradient of concrete structures. At present, common hydration heat inhibitors are mostly esterified modified products of starch polysaccharides or a combination of various organic / inorganic retarders. In the construction process of large-volume concrete, the use of hydration heat inhibitors is mainly convenient and efficient, but most of the hydration heat inhibitors on the market are powders, which are prone to uneven dispersion and affect the use effect. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a preparation method and application of an aqueous Pickering emulsion type hydration heat inhibition material.

[0005] The present application provides a hydration heat inhibition material, which specifically includes the following components in parts by weight: 90-110 parts of water, 5-20 parts of oil phase cosolvent, 0.1-0.7 parts of solubilizer, 20-100 parts of colloidal emulsifier, and 0.5-15 parts of oil phase component;

[0006] The oil phase component is prepared from anhydride, diol, polymerization inhibitor and catalyst in a molar ratio of 0.5-3:1:0.01-0.15:0.05-0.55.

[0007] The hydration heat inhibition material prepared in the present application has good stability. The use of the material is not affected by the ambient temperature. The hydration heat release rate peak value, hydration heat cumulative heat release and adiabatic temperature rise peak value of the hydration heat inhibition material during the application process are greatly reduced. While having the ability to inhibit cement hydration heat, it has little effect on the strength of concrete.

[0008] The hydration heat inhibition material described in the present application is an aqueous Pickering emulsion, which is mainly composed of two materials: an oil phase and a colloidal particle emulsifier, wherein the oil phase is a multiester esterification product, and the colloidal particle emulsifier is a nano-retardant gel or suspension, which can be adsorbed on the oil-water interface to wrap the oil phase. When acting between cement pastes, on the one hand, the adsorption capacity of the colloidal particles with the oil phase will be weakened under alkaline conditions, slowly dispersed between the pastes, and chelated with the metal ions generated during the cement hydration process to form a stable complex, thereby preventing the cement hydration reaction from proceeding; on the other hand, after the colloidal shell is dispersed, the oil phase is slowly released, and the ester group contained therein (the ester group content can be regulated by regulating the molecular weight of the oil phase, and then the degree of hydration inhibition of the hydration heat inhibition material) is also gradually hydrolyzed under alkaline conditions, releasing a large number of carboxyl groups, which are again complexed with the metal ions generated by cement hydration to form a stable complex, delaying and reducing the hydration products generated during the cement hydration acceleration period, thereby inhibiting the heat release of cement hydration and reducing the temperature cracks caused by uneven internal temperature of large-volume concrete.

[0009] Preferably, the hydration heat inhibition material specifically comprises the following components in parts by weight: 95-105 parts of water, 8-15 parts of oil phase cosolvent, 0.2-0.6 parts of solubilizer, 30-60 parts of colloidal emulsifier, and 3-7 parts of oil phase component.

[0010] Preferably, the oil phase component is prepared from anhydride, diol, inhibitor and catalyst in a molar ratio of 1-2:1:0.08-0.12:0.08-0.15.

[0011] Preferably, the preparation method of the oil phase component is: mix the acid anhydride, diol and inhibitor, add water to adjust the solution concentration to 60-100%, mix evenly, and heat; when the temperature rises to 60-90°C, immediately add the catalyst, and at the same time introduce nitrogen to remove the moisture generated during the reaction; raise the temperature to 110-120°C again, keep warm for 2-8h, and cool to room temperature after the reaction is completed to obtain the oil phase component.

[0012] Preferably, the oil phase co-solvent is selected from one or more of tetrafluoroethylene, cyclohexane, acetone and ethyl acetate.

[0013] Preferably, the solubilizing agent is selected from one or more of γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and γ-methacryloxypropyltrimethoxysilane.

[0014] Preferably, the colloidal emulsifier is selected from one or more of nano carboxymethyl chitosan colloidal dispersion, nano dextrin microsphere dispersion, and nano sodium alginate dispersion.

[0015] Preferably, in the oil phase components:

[0016] The acid anhydride is selected from one or more of maleic anhydride, succinic anhydride, phthalic anhydride, benzoic anhydride, etc.;

[0017] The diol is selected from one or more of ethylene glycol and polyethylene glycol with a molecular weight of 100-600;

[0018] The polymerization inhibitor is selected from one or more of phenothiazine, hydroquinone, p-hydroxyanisole, 2-tert-butylhydroquinone, and 2,4-dinitro-p-cresol;

[0019] The catalyst is selected from one or more of p-toluenesulfonic acid, methanesulfonic acid and 4-dimethylaminopyridine.

[0020] In a second aspect, the present application provides a method for preparing the above-mentioned hydration heat inhibition material, which specifically includes the following steps in sequence: the water, the oil phase co-solvent, the solubilizer and the colloidal emulsifier are mixed evenly in proportion and then added to an emulsifying device for shear emulsification for 5-20 minutes at a shear rate of 3000-10000 r / min, and the oil phase components are slowly added in batches during the shearing process; after the shear emulsification is completed, a hydration heat inhibition material intermediate is obtained; then the hydration heat inhibition material intermediate is ultrasonically treated with an ultrasonic disperser for 5-20 minutes, and the surface floating matter is filtered to remove, so as to obtain the hydration heat inhibition material.

[0021] In a third aspect, the present application provides the application of the above-mentioned hydration heat inhibition material in the field of preparing concrete.

[0022] In summary, the technical solution of this application has the following effects:

[0023] The hydration heat inhibition material prepared by the technical solution provided in the present application has good stability; compared with the blank group without using the hydration heat inhibition material, the peak value of the hydration heat release rate, the cumulative hydration heat release and the peak value of the adiabatic temperature rise in the embodiment of the hydration heat inhibition material prepared by the present application are greatly reduced, and the strength reduction value is small. DETAILED DESCRIPTION

[0024] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.

[0025] Example

[0026] Examples 1-5

[0027] Embodiments 1-5 each provide a hydration heat inhibition material.

[0028] The difference between the above embodiments is that the dosage of each raw material component is different, as shown in Table 1.

[0029] The preparation method of the hydration heat inhibition material in the above embodiment is specifically as follows:

[0030] Preparation of the oil phase component: Add 1.30 mol of 127.6 g of maleic anhydride, 1 mol of 62 g of ethylene glycol, 0.05 mol of 5.5 g of inhibitor hydroquinone and 36 g of deionized water to the bottom of a four-necked flask with a condensation and water-carrying device and heat. When the temperature rises to 75°C, immediately add 0.1 mol of 17.2 g of catalyst p-toluenesulfonic acid, and at the same time, introduce nitrogen to remove the moisture generated during the reaction. Raise the temperature to 115°C again and keep the reaction warm for 6 hours. After the reaction is completed, cool to room temperature to obtain the oil phase component of the hydration heat inhibition material.

[0031] Preparation of hydration heat inhibition material: according to the amounts in Table 1, deionized water, oil phase cosolvent tetrafluorofuran, solubilizer γ-glycidyloxypropyltrimethoxysilane and colloidal emulsifier nano carboxymethyl chitosan colloidal dispersion (concentration of 70%) were mixed evenly, added into an emulsifying device and shear emulsified at a rate of 5000r / min for 20min using a high-speed shear emulsifier, and the oil phase components of the hydration heat inhibition material prepared above were slowly added in batches during the shearing process, and a hydration heat inhibition material intermediate was obtained after the shear emulsification was completed; the hydration heat inhibition material intermediate was then ultrasonically treated for 10min using an ultrasonic disperser (350W), and the hydration heat inhibition material was obtained after filtering to remove surface floating matter.

[0032] Table 1 Amount of each component in the hydration heat inhibition material in Examples 1-5 and Comparative Examples 1-2

[0033]

[0034] Embodiment 6-9

[0035] Examples 6-9 each provide a hydration heat inhibition material.

[0036] The difference between the above embodiment and embodiment 3 is that the types of raw material components in the hydration heat inhibition material are specifically shown below.

[0037] In Example 6: the oil phase co-solvent is ethyl acetate.

[0038] In Example 7: the oil phase co-solvent is cyclohexane.

[0039] In Example 8: the solubilizing agent is γ-aminopropyltriethoxysilane.

[0040] In Example 9: the solubilizing agent is γ-methacryloxypropyltrimethoxysilane.

[0041] The remaining process parameters in the above embodiment are the same as those in embodiment 3.

[0042] Examples 10-14

[0043] Examples 10-14 each provide a hydration heat inhibition material.

[0044] The difference between the above embodiment and embodiment 3 is that the preparation method of the oil phase component is specifically as follows.

[0045] In Example 10: During the preparation of the oil phase component, 1.3 mol of succinic anhydride was used instead of maleic anhydride.

[0046] In Example 11: During the preparation of the oil phase component, ethylene glycol was replaced by 1 mol of polyethylene glycol with a molecular weight of 100.

[0047] In Example 12: During the preparation of the oil phase component, ethylene glycol was replaced by 1 mol of polyethylene glycol having a molecular weight of 400.

[0048] In Example 13: During the preparation of the oil phase component, ethylene glycol was replaced with 1 mol of polyethylene glycol having a molecular weight of 600.

[0049] In Example 14: During the preparation of the oil phase component, 0.05 mol of p-hydroxyanisole was used instead of hydroquinone as the polymerization inhibitor.

[0050] The remaining process parameters in the above embodiment are the same as those in embodiment 3. Embodiment 15

[0051] This embodiment provides a hydration heat inhibition material.

[0052] The preparation method of the hydration heat inhibition material in this embodiment is specifically as follows:

[0053] Preparation of the oil phase component: 174 g of maleic anhydride, 200 g of polyethylene glycol with a molecular weight of 200, and 9.9 g of phenothiazine are added to the bottom of a four-necked flask with a condensation and water-carrying device and heated. When the temperature rises to 60°C, 10.4 g of methylsulfonic acid is immediately added, and nitrogen is introduced at the same time to remove the moisture generated during the reaction. The temperature is raised to 120°C again and kept warm for 6 hours. After the reaction is completed, it is cooled to room temperature to obtain the oil phase component of the hydration heat inhibition material.

[0054] 100g of deionized water, 8g of cyclohexane, 0.1g of γ-glycidyloxypropyltrimethoxysilane and 35g of nanodextrin microsphere dispersion were mixed evenly and added into an emulsifying device. The mixture was sheared and emulsified for 8min at a rate of 5500r / min using a high-speed shear emulsifier. During the shearing process, 10g of the oil phase component of the hydration heat inhibition material was slowly added in batches. After the shearing emulsification was completed, a hydration heat inhibition material intermediate was obtained. The hydration heat inhibition material intermediate was then ultrasonically treated for 8min using an ultrasonic disperser. The hydration heat inhibition material was obtained after filtering to remove surface floating matter. Example 16

[0055] This embodiment provides a hydration heat inhibition material.

[0056] The preparation method of the hydration heat inhibition material in this embodiment is specifically as follows:

[0057] Preparation of the oil phase component: 116 g of succinic anhydride, 200 g of polyethylene glycol with a molecular weight of 200, and 10.4 g of hydroquinone are added to the bottom of a four-necked flask with a condensation and water-carrying device and heated. When the temperature rises to 65°C, 15.2 g of p-toluenesulfonic acid is immediately added, and nitrogen is introduced at the same time to remove the moisture generated during the reaction. The temperature is raised to 120°C again and kept warm for 6 hours. After the reaction is completed, it is cooled to room temperature to obtain the oil phase component of the hydration heat inhibition material.

[0058] 100g of deionized water, 5g of tetrafluoroethylene, 0.18g of γ-aminopropyltriethoxysilane and 40g of nano-carboxymethyl chitosan colloidal dispersion were mixed evenly and added into an emulsifying device. The mixture was sheared and emulsified for 5min at a rate of 7000r / min using a high-speed shear emulsifier. During the shearing process, 15g of the oil phase component of the hydration heat inhibition material was slowly added in batches. After the shearing emulsification was completed, the hydration heat inhibition material intermediate was obtained. The hydration heat inhibition material intermediate was then ultrasonically treated for 5min using an ultrasonic disperser. The hydration heat inhibition material was obtained after filtering to remove the floating matter on the surface. Embodiment 17

[0059] This embodiment provides a hydration heat inhibition material.

[0060] The preparation method of the hydration heat inhibition material in this embodiment is specifically as follows:

[0061] Preparation of the oil phase component: Add 105g of benzoic anhydride, 100g of ethylene glycol, and 11.1g of hydroquinone to the bottom of a four-necked flask with a condenser and water device and heat it. When the temperature rises to 65°C, immediately add 14.9g of p-toluenesulfonic acid, and at the same time, introduce nitrogen to remove the moisture generated during the reaction. Raise the temperature to 120°C again and keep the reaction warm for 5h. After the reaction is completed, cool to room temperature to obtain the oil phase component of the hydration heat inhibition material.

[0062] 100g of deionized water, 7g of ethyl acetate, 0.2g of γ-methacryloxypropyltrimethoxysilane and 45g of nano-carboxymethyl chitosan colloidal dispersion were mixed evenly and added into an emulsifying device and shear emulsified for 7min at a rate of 6500r / min using a high-speed shear emulsifier, and 20g of the oil phase component of the hydration heat inhibition material was slowly added in batches during the shearing process, and the hydration heat inhibition material intermediate was obtained after the shear emulsification was completed; the hydration heat inhibition material intermediate was then ultrasonically treated for 8min using an ultrasonic disperser, and the hydration heat inhibition material was obtained after filtering to remove surface floating matter. Comparative Example

[0063] Comparative Example 1-2

[0064] Comparative Examples 1-2 each provide a hydration heat inhibition material.

[0065] The difference between the comparative example and Example 3 is that the dosage of the raw material components in the hydration heat inhibition material is specifically shown in Table 1.

[0066] The remaining process parameters in the above comparative example are the same as those in Example 3. Comparative Example 3

[0067] This comparative example provides a hydration heat inhibiting material.

[0068] The preparation method of the hydration heat inhibition material in this comparative example is specifically as follows:

[0069] 127.6g maleic anhydride 1.30mol, 62g ethylene glycol 1mol, 5.5g inhibitor hydroquinone 0.05mol and 36g deionized water were added to the bottom of a four-necked flask with a condensation and water-carrying device and heated. When the temperature rose to 75°C, 17.2g catalyst p-toluenesulfonic acid 0.1mol was immediately added, and nitrogen was introduced to remove the water generated during the reaction. The temperature was raised to 115°C again and kept warm for 6h. After the reaction was completed, it was cooled to room temperature to obtain a hydration heat inhibition material. (The oil phase component of the hydration heat inhibition material in Example 1 was used as the hydration heat inhibition material). Comparative Example 4

[0070] This comparative example provides a hydration heat inhibiting material.

[0071] The difference between this comparative example and Example 3 is that an equal amount of micron carboxymethyl chitosan colloidal dispersion is used instead of nanometer carboxymethyl chitosan colloidal dispersion as the colloidal emulsifier.

[0072] The remaining process parameters in this comparative example are the same as those in Example 3. Comparative Example 5

[0073] This comparative example provides a hydration heat inhibiting material.

[0074] In this comparative example, nano-carboxymethyl chitosan colloidal dispersion (concentration of 70%) is used as the hydration heat inhibition material. Comparative Example 6

[0075] This comparative example provides a hydration heat inhibiting material.

[0076] In this comparative example, sodium gluconate, a common sugar retarder, is used as the hydration heat inhibition material.

[0077] Performance testing

[0078] Stability: Store the obtained hydration heat inhibition material at room temperature. After a period of time, observe whether there is precipitation at the bottom and record the number of days.

[0079] Cement hydration heat (peak hydration heat release rate and cumulative hydration heat release): The cement hydration heat test method is carried out in accordance with GB / T 2022-1980 "Cement hydration heat test method (direct method)", and the initial measurement temperature is 20°C;

[0080] Adiabatic temperature rise peak: dig a 150mm×150mm×150mm hole test mold in the center of the insulation foam board, pour the mixed mortar into the test mold, then place the temperature sensor's temperature measuring head in the center of the mortar in the test mold, and finally seal the exposed part of the test mold with another insulation foam board, and record the temperature change and temperature peak in real time.

[0081] Strength: Concrete compressive strength is tested according to GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". The concrete mix ratio is: cement 267kg / m 3 , fly ash 78kg / m 3 , mineral powder 36kg / m 3 , sand 875kg / m 3 , stone 1020kg / m 3 , water 150.1kg / m 3 The fly ash is first-grade fly ash, the fineness modulus of sand is 2.6, and the continuous grading of stone is 4.75mm-16mm.

[0082] The blank group was taken without adding hydration heat inhibition material.

[0083] Test results: as shown in Table 2.

[0084] Table 2 Performance test results of hydration heat inhibition materials in Examples and Comparative Examples

[0085]

[0086] It can be seen from the test data in Table 2 that in the process of preparing the hydration heat inhibition material in Comparative Examples 1-2, the dosage of each raw material component is not matched, and the peak value of the hydration heat release rate, the cumulative hydration heat release and the adiabatic temperature rise peak all decrease by a small margin; and the strength reduction value in Comparative Example 2 is large, and the application effect is poor.

[0087] The particle size of the emulsified shell used in Comparative Example 3 is relatively large and is not easily adsorbed and wrapped by the oil phase. Therefore, it stratifies in a short period of time and has poor stability. In actual application, the peak value of the hydration heat release rate, the cumulative hydration heat release and the adiabatic temperature rise peak all decrease by a small margin.

[0088] In Comparative Example 4, an equal amount of micron carboxymethyl chitosan colloidal dispersion was used instead of nano carboxymethyl chitosan colloidal dispersion as the colloidal emulsifier, and the hydration heat inhibition material prepared had a smaller decrease in the hydration heat release rate peak, hydration heat cumulative heat release and adiabatic temperature rise peak during actual application.

[0089] Comparative Example 5 directly uses nano-carboxymethyl chitosan colloidal dispersion (concentration of 70%) as the hydration heat inhibition material, which has poor stability, and the peak hydration heat release rate, hydration heat cumulative heat release and adiabatic temperature rise peak values ​​all decrease slightly during actual application.

[0090] Comparative Example 6 uses sodium gluconate, a common sugar retarder, as the hydration heat inhibition material, and the strength reduction value is relatively high during actual application.

[0091] In contrast, the hydration heat inhibition material prepared by the technical solution provided in the present application has good stability; compared with the blank group without using the hydration heat inhibition material, the peak value of the hydration heat release rate, the cumulative hydration heat release and the peak value of the adiabatic temperature rise in the embodiment of the hydration heat inhibition material prepared by the present application are greatly reduced, and the strength reduction value is small.

[0092] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A hydration heat inhibition material, characterized in that: Specifically, it includes the following components in parts by weight: 90-110 parts of water, 5-20 parts of oil phase cosolvent, 0.1-0.7 parts of solubilizer, 20-100 parts of colloidal emulsifier, and 0.5-15 parts of oil phase component; The oil phase component is prepared from anhydride, diol, inhibitor and catalyst in a molar ratio of 0.5-3:1:0.01-0.15:0.05-0.55; The preparation method of the oil phase component is as follows: an acid anhydride, a diol and a polymerization inhibitor are mixed, water is added to adjust the solution concentration to 60-100%, the mixture is evenly mixed, and the mixture is heated; when the temperature rises to 60-90° C., a catalyst is immediately added, and nitrogen is introduced to remove the water generated during the reaction; the temperature is raised to 110-120° C. again, the temperature is kept for 2-8 hours, and after the reaction is completed, the mixture is cooled to room temperature to obtain the oil phase component; The colloidal emulsifier is selected from one or more of nano carboxymethyl chitosan colloidal dispersion, nano dextrin microsphere dispersion, and nano sodium alginate dispersion; The hydration heat inhibition material is an aqueous Pickering emulsion.

2. The hydration heat suppression material according to claim 1, characterized in that: Specifically, the composition comprises the following components in parts by weight: 95-105 parts of water, 8-15 parts of oil phase cosolvent, 0.2-0.6 parts of solubilizer, 30-60 parts of colloidal emulsifier and 3-7 parts of oil phase component.

3. The hydration heat suppression material according to claim 1, characterized in that: The oil phase component is prepared from anhydride, diol, polymerization inhibitor and catalyst in a molar ratio of 1-2:1:0.08-0.12:0.08-0.

15.

4. The hydration heat suppression material according to claim 1, characterized in that: The oil phase co-solvent is selected from one or more of tetrafluoroethylene, cyclohexane, acetone and ethyl acetate.

5. The hydration heat suppression material according to claim 1, characterized in that: The solubilizing agent is selected from one or more of γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and γ-methacryloxypropyltrimethoxysilane.

6. The hydration heat suppression material according to claim 1, characterized in that: In the oil phase components: The acid anhydride is selected from one or more of maleic anhydride, succinic anhydride, phthalic anhydride and benzoic anhydride; The diol is selected from one or more of ethylene glycol and polyethylene glycol with a molecular weight of 100-600; The polymerization inhibitor is selected from one or more of phenothiazine, hydroquinone, p-hydroxyanisole, 2-tert-butylhydroquinone, and 2,4-dinitro-p-cresol; The catalyst is selected from one or more of p-toluenesulfonic acid, methanesulfonic acid and 4-dimethylaminopyridine.

7. The method for preparing the hydration heat inhibition material according to any one of claims 1 to 6, characterized in that: Specifically, the method comprises the following steps: uniformly mixing the water, the oil phase cosolvent, the solubilizer and the colloidal emulsifier in proportion, adding the mixture into an emulsifying device, performing shear emulsification for 5-20 minutes at a shear rate of 3000-10000 r / min, and slowly adding the oil phase components in batches during the shearing process; after the shear emulsification is completed, a hydration heat inhibition material intermediate is obtained; and then the hydration heat inhibition material intermediate is subjected to ultrasonic treatment for 5-20 minutes using an ultrasonic disperser, and floating objects on the surface are removed by filtering to obtain the hydration heat inhibition material.

8. Use of the hydration heat inhibiting material according to any one of claims 1 to 6 in the field of preparing concrete.

Citation Information

Patent Citations

  • Hydration heat inhibitory concrete expansion agent

    CN109836070A

  • Ester polycarboxylic acid water reducer with low hydration heat and preparation method thereof

    CN114106261A